Compost barns in Brazilian Subtropical region (Part 1): facility, barn management and herd characteristics (Research, Society and Development, 2020)
The objective of this study was to describe barn management practices and to evaluating cow locomotion, hygiene and hock lesion prevalence of dairy cows housed in Compost Barns (CB) located in the subtropical region of Brazil. The CB has demonstrated satisfactory results in relation to animal comfort and productivity. However, modifications to the initial American recommendations are being made by producers in order to adapt it to different conditions. Thirty dairy farms were analyzed regarding structural measurements and layout, management practices, bedded pack and herd characteristics. The main results highlighted were the resting space of 14.6 m2 cow-1, most of the farms (87%) had newly built facilities and only 43.3% were built in E-W direction. Most farms did not have ridge opening and 60 % had fans in the bedded pack area, which is mostly stirred twice a day. About a third of the farms used CB only during the hottest hours of the day or rainy periods, with pasture access the remainder of the time. The bedded pack material averaged 48.4% DM, pH of 8.68, C:N of 5.90 and deep bedding temperature of 42.52 ⁰C. Locomotion scoring showed majority of the cows with  a normal gait (95.5% of cows scoring 1 or 2 for locomotion). Hock lesions were observed in 15.5% of the animals and 84.0% of the cows were clean or only slightly dirty. This study indicates characteristics or issues to start an improvement process on CB usage in Brazilian subtropical region. The cow comfort was considered adequate, based on results of cow locomotion, lesions and hygiene scoring.